2016
DOI: 10.6007/ijarems/v4-i4/2061
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Stock Market on Economic Growth: The Case of Iran

Abstract: The main goal of this paper is to investigate the relationship between stock market development and economic growth in Iran. To this end, the paper using quarterly data from 1998Q1 to 2012Q4 and employing time series methodologies, namely Johansen's cointegration and Granger causality testing procedures in the context of Vector Error Correction Models (VECM), examine the short and long run dynamics of the relationship. The Johansen test of co-integration suggests that variables are co-integrated and the VECM r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Besides, Demirguc-Kunt and Levine (1996) reinforced this segmentation by drawing attention to the increased flow of equity investments to emerging markets. However, the literature is inundated with arguments that economic growth is impacted by several factors: financial markets (Ngongang, 2015;Hassan et al, 2016;Puryan, 2017;Njemcevic, 2017); stock market (Acquah-Sam and Salami, 2014;Njogo and Ogunlowore, 2014;Yadirichukwu and Chigbu, 2014;Niranjala, 2015;Khan and Ahmed, 2015;Khyareh and Oskou, 2015;Jareno and Negrut, 2016;Nordin and Nordin, 2016;Taiwo et al, 2016) and banks (Ngongang, 2015;Puryan, 2017. The main argument regarding market opening in recent times revolves around allowing greater participation by international investors in domestic markets (Patro, 2005) while Pagano (1993) showed that financial intermediation has both level and growth effects; adding, however, that the resulting models have offered important insights into the effect of financial development on growth and vice versa. Odo et al (2017) argued that in traditional growth theory, the growth rate is a positive function of exogenous technical progress, but at the same time acknowledge that endogenous growth models on the other hand show that economic growth performance is related to financial development, technology and income distribution.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, Demirguc-Kunt and Levine (1996) reinforced this segmentation by drawing attention to the increased flow of equity investments to emerging markets. However, the literature is inundated with arguments that economic growth is impacted by several factors: financial markets (Ngongang, 2015;Hassan et al, 2016;Puryan, 2017;Njemcevic, 2017); stock market (Acquah-Sam and Salami, 2014;Njogo and Ogunlowore, 2014;Yadirichukwu and Chigbu, 2014;Niranjala, 2015;Khan and Ahmed, 2015;Khyareh and Oskou, 2015;Jareno and Negrut, 2016;Nordin and Nordin, 2016;Taiwo et al, 2016) and banks (Ngongang, 2015;Puryan, 2017. The main argument regarding market opening in recent times revolves around allowing greater participation by international investors in domestic markets (Patro, 2005) while Pagano (1993) showed that financial intermediation has both level and growth effects; adding, however, that the resulting models have offered important insights into the effect of financial development on growth and vice versa. Odo et al (2017) argued that in traditional growth theory, the growth rate is a positive function of exogenous technical progress, but at the same time acknowledge that endogenous growth models on the other hand show that economic growth performance is related to financial development, technology and income distribution.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Stock market development which shows the size of the stock market was measured by the ratio of market capitalization to GDP and we believe that this measure provides a clearer picture of how the stock market impacts economic growth. This measure was similarly used by Khyareh and Oskou (2015). Also, Levine and Zervos (1998) explained that the market capitalization ratio equals the value of listed shares divided by GDP and was used by them as a measure of market size.…”
Section: Definition and Measurement Of Variablesmentioning
confidence: 99%
“…As per the study of Khyareh and Oskou (2015), the objective of this paper is to examine the relationship between the creation of the stock market and Iran's economic growth. The paper explores the short and long-term dynamics of the relationship using quarterly data from 1998Q1 to 2012Q4 and using time series methodologies, including Johansen's co-integration, Vector error correction model, and Granger causality testing procedures.…”
Section: Literature Reviewmentioning
confidence: 99%